New Freshwater Aquaculture Systems in the Red River Delta of Vietnam: Evolution of a Key Role in Food Systems and Rural Development. Issue 2 (1st March 2017) - Van Huong, Nguyen; Cuong, Tran Huu; Thu, Tran Thi Nang; Lebailly, Philippe
Abstract : Freshwater aquaculture production systems are closely related to Integrated Agriculture Aquaculture systems. The systems are traditionally integrated with crop production, horticulture, and livestock husbandry. Improved aquaculture systems are currently able to not only improve the nutrients of local farmers' diets and economic conditions, but are also able to create employment opportunities and lead to better resource‐utilization and rural development. This paper aims to present the changes in food systems affected by the rapidly developing freshwater aquaculture in northern Vietnam. It will shed light on how the aquaculture system plays various roles in supporting agrarian livelihoods, their relationships to well‐being, and food security using a clear example of small‐scale aquaculture in a province of the Red River Delta. The challenges and opportunities presented to small‐scale producers and culture systems are assessed, and the likely future of small‐scale freshwater production systems is discussed and forecast. Combining historical, adaptive, and systematic approaches, the study revealed the features and characteristics of inland aquaculture systems at the household level over a decade of the evolutionary process (1997–2015). By investigating 151 aquaculture households in two representative districts of the region, the three existing systems are identified: VAC system (23%) (whereby V=vuon‐gardens (horticulture), A=Ao‐ponds (aquaculture) and C=Chuong‐animal sheds/pens (livestock husbandry)); aquaculture/livestock (AF) system (43%); and the commercially intensive fish culture (FS) system (34%). Beyond the positive benefits to the food system and rural development, potential considerably exists for further aquaculture integration within VAC systems in the region, which will contribute to poverty reduction and improvement of the livelihoods of small‐scale rural farmers.